Technical Efficiency Analysis of Non-Chemical Pesticide Rice Farming in Rejoasri Village, Seputih Raman District - Sutarni, Sutarni; Fitriani, Fitriani; Berliana, Dayang; Andarwangi, Tunjung (ABEC Indonesia, 2024)
Rejoasri Village, Seputih Raman District, is one of the villages that implements sustainable agricultural practices, namely non-chemical pesticide rice farming that produces rice free of chemical pesticide residue "Berasera". The problem faced in farming is the low productivity of paddy fields so that the level of technical efficiency of rice farming is also low. This will cause economic sustainability to also be low. The objectives of this study are (1) Analyze the factors that affect the production of non-chemical pesticide paddy paddy farming, (2) Analyze the level of technical efficiency of non-chemical pesticide paddy paddy farming, and (3) Analyze the determinants of in-efficiency of non-chemical pesticide paddy paddy farming in Seputih Raman District, Central Lampung Regency. This research will be carried out in Rejoasri Village, Seputih Raman District, Central Lampung Regency. The research sample was taken as many as 30 people. The research data will be analyzed in a qualitative and quantitative descriptive manner. The data will be tabulated, analyzed mathematically, and analyzed statistically according to the research objectives. Itwill be processed using a computer using frontier software version 4.1. The first, second, and third research objectives were analyzed using the stochastic frontier production function approach. The technical efficiency for a farmer ranges from zero to one or the Technical Efficiency (TEi) value is 0 ≤ TEi ≤ 1. The results showed that the factors that had a significant effect on the production of non-chemical pesticide rice were the area of agricultural land (X1), organic fertilizer (X4), and vegetable pesticides (X5), while the factors that did not have a significant effect on the production of non-chemical pesticide rice were the Seed variable (X2), the inorganic fertilizer variable (X3), and the rice farming labor variable (X6). The average value of technical efficiency of non-chemical pesticide rice production in the region is 0.8737, which means that the cultivation of non-chemical pesticide rice has been efficient, because the technical efficiency value is with an average of > 0.7000. There are 86.6667% of farmers who have achieved technical efficiency, and as many as 13.3333% of farmers have not achieved technical efficiency in the non-chemical pesticide rice business. Significant factors affecting the technical inefficiency of non-chemical pesticide rice farming are age, education, and experience in non-chemical pesticide rice farming.